Epistemologi Pemikiran Gabriel Said Reynolds tentang Konsep Homili Al-Qur’an - Haiva Satriana Zahrah (Islamic Religious Education Departement, 2024)
This study examines the epistemology of Reynolds' thought, which initiated the concept of discourse to read (understand) the Qur'an. Reynolds made a new formulation by seeing the pattern of connectedness between texts and trying to break the argument that considered the Qur'an an imitation text from the Jewish and Christian traditions. This study aims to describe the discourse initiated by Reynolds, review the epistemology of his thoughts, and explain the implications of this concept. This research is a qualitative study in the form of library research using the Qur'an and its biblical subtext as the primary data source and a theoretical hermeneutic approach as an analytical tool in reviewing the book. The results of this study indicate that the Qur'an with pre-Quranic texts has a different literary genre; on the other hand, the Qur'an has a homily nature in developing its religious values. The concept of this homily carries methodological consequences for reading or interpreting the Qur'an with previous texts, namely the apocryphal Bible and Jewish and Christian exegetical works. Methodologically, Reynolds used alliterative theory and a literary approach. The concept of discourse has implications for assessing the Bible so that they are mindlessly suspicious of it, and using the Bible as a source or reference can be an alternative to understanding the Qur'an.